Investigating the Interaction between Methanol and the Heulandite-type Zeolite using First Principle Molecular Dynamic - Fiska Dewi Wulandhani; Fajar Inggit Pambudi (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The interaction between methanol and the Heulandite-type zeolite has been unveiled to give an atomic scale detail regarding the catalytic activity of this zeolite for methanol conversion. The study was carried out by first principle molecular dynamics to get an insight into the structure and electronic behaviour of methanol inside the zeolite structure at different temperatures. The behaviour of methanol was studied when the location of the proton of Bronsted acid sites was varied to give both possible direct and less interaction with methanol. The results show that methanol interacts with the proton from zeolite to give a cationic species of [CH3OH2]+ both in 300K and 573K conditions. However, when the proton is located at different location far from possible interaction with methanol, the formation of a cationic species is hindered. This study provides an insight into the design of Heulandite type zeolite to give a catalytic activity toward methanol transformation.